Sub-6G Metamaterial-Based Flexible Wearable UWB Antenna for IoT and WBAN - Saeidi, T. (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper presents a metamaterial-based flexible wearable ultra-wideband antenna at sub-6G frequency bands applied to the Internet of things (IoT) and wireless body area network (WBAN) applications. The miniaturized proposed wearable antenna comprises two layers of denim (10 Ã 10 mm2) and felt (10 Ã 15 mm2). Furthermore, the elliptical patch is loaded with an L-shaped slot, a stub at the back, and chamfered ground to remove the stopbands and improve the bandwidth (BW). Then, the antenna is integrated with 6 arrays of modified grain rice shape within a Split ring resonator (SRR) to enhance the bandwidth, gain, and directivity. The proposed antenna presents a broad BW (6.5-35 GHz), maximum gain and directivity of 8.85 dBi and 10 dBi, and > 80 efficiency over its operating frequency band. Besides, the antenna shows good agreement between the simulated and measured results offering better performance as compared to the similar existing antennas while showing smaller dimensions. Â© 2020 IEEE.